Pelatihan Penyusunan Lembar Kegiatan Siswa (LKS) Matematika Berbantuan Geogebra Training to Create Mathematics Student Activity Sheet Using Geogebra - Atmini Dhoruri; Sugiyono Sugiyono; Endah Retnowati; Dwi Lestari; Eminugroho Ratna Sari (Yogyakarta State University, 2018)
Student Activity Sheet (LKS) is one of the teaching materials that should be prepared by the teacher to improve the quality of learning. Especially for math teachers, LKS which is completed with graphical visualization can improve students' enthusiasm. Software that is quite easy but with a complete feature is Geogebra. Therefore, the purpose of the training is for the preparation of Geogebra-assisted LKS.This training is in the form of demonstration activity of Geogebra both 2D and 3D for material of geometry, algebra, and calculus. The activity continued with the assistance to the participants by first forming the participants into several groups. Activities are inserted with evaluation and reflection so that participants' needs can be accommodated. Apart from the technical use of Geogebra, the participants are also equipped with theory and motivation for the development of teaching materials.Based on the questionnaire results, a total of 65.38% of participants considered that the training activities are very motivating in improving the implementation of learning in schools. Participants also respond very well in terms of the usefulness of this training and expect continued activities.